Aberrant attentional modulation of the auditory steady state response (ASSR) is related to auditory hallucination severity in the first-episode schizophrenia-spectrum. (July 2022) - Coffman, Brian A.; Ren, Xi; Longenecker, Julia; Torrence, Natasha; Fishel, Vanessa; Seebold, Dylan; Wang, Yiming; Curtis, Mark; Salisbury, Dean F.
Abstract: The 40-Hz auditory steady state response (ASSR) is reduced early in schizophrenia, with differences evident even at the first episode of schizophrenia-spectrum psychosis (FESz). Although robust, there is high variability in effect size across studies, possibly due to differences in experimental control of attention and heterogeneity of symptom profiles across studies, both of which may affect the ASSR. We investigated the relationships among ASSR deficits, attention-mediated sensory gain, and auditory hallucinations in 25 FESz (15 male; 23.3 ± 4.5 years) and 32 matched healthy comparison subjects (HC, 22 male; 24.7 ± 5.8 years). ASSR was measured to 40-Hz click trains at three intensities (75, 80, and 85 dB) while participants attended or ignored stimuli. ASSR evoked power and inter-trial phase coherence (ITPC) were measured using the Morlet wavelet transform. FESz did not show overall ASSR power reduction (p > 0.1), but power was significantly increased with attention in HC (p < 0.01), but not in FESz (p > 0.1). Likewise, FESz did not evince overall ASSR ITPC reduction (p > 0.1), and ITPC was significantly increased with attention in HC (p < 0.01), but not in FESz (p > 0.09). Attention-related change in ASSR correlated with auditory hallucination severity for power (r = −0.49, p < 0.05) and ITPC (r = −0.58, p < 0.01). FESz with auditory hallucinations may have pathologically increased basal excitability of auditory cortex and consequent reduced ability to further increase auditory cortex sensory gain with focused attention. These findings indicate hallucination-related pathophysiology early in schizophrenia and may guide novel intervention strategies aimed to modulate basal activity levels.